20-2(2w+1)=5w-2(5+w)

Simple and best practice solution for 20-2(2w+1)=5w-2(5+w) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20-2(2w+1)=5w-2(5+w) equation:


Simplifying
20 + -2(2w + 1) = 5w + -2(5 + w)

Reorder the terms:
20 + -2(1 + 2w) = 5w + -2(5 + w)
20 + (1 * -2 + 2w * -2) = 5w + -2(5 + w)
20 + (-2 + -4w) = 5w + -2(5 + w)

Combine like terms: 20 + -2 = 18
18 + -4w = 5w + -2(5 + w)
18 + -4w = 5w + (5 * -2 + w * -2)
18 + -4w = 5w + (-10 + -2w)

Reorder the terms:
18 + -4w = -10 + 5w + -2w

Combine like terms: 5w + -2w = 3w
18 + -4w = -10 + 3w

Solving
18 + -4w = -10 + 3w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-3w' to each side of the equation.
18 + -4w + -3w = -10 + 3w + -3w

Combine like terms: -4w + -3w = -7w
18 + -7w = -10 + 3w + -3w

Combine like terms: 3w + -3w = 0
18 + -7w = -10 + 0
18 + -7w = -10

Add '-18' to each side of the equation.
18 + -18 + -7w = -10 + -18

Combine like terms: 18 + -18 = 0
0 + -7w = -10 + -18
-7w = -10 + -18

Combine like terms: -10 + -18 = -28
-7w = -28

Divide each side by '-7'.
w = 4

Simplifying
w = 4

See similar equations:

| 0*3+4=0*2+3 | | n+9=3n+5*4 | | f/7-8=72 | | 8(t+2)-3(t-4)=6(t-7) | | 6-9x=26-23x | | 2x-175=755 | | 26.6x+76.6x+200x=5513 | | 2x+11=-37-10 | | 60=12x | | 5x+4=4555 | | 8x-8y=-16 | | 2x+5x/9=-30 | | f+13=27 | | 7=q-83 | | 6n-4(n-3)=n+3 | | 3x+7=(5x-4)*2 | | 9+(2/3)x=81 | | -7c(3/4)=65 | | 6-4y=y | | 2a-3=3-4a | | 3a-6=10-a | | (2x-2)2=(3x-2)(x-3) | | 24+2x-x^2= | | 132-6x=2x-20 | | 12x-5=8x-x | | x(p-cv)=cf | | 4t-3=-13-2t | | 5.3+9.2x=7-4x-8.8 | | 1.8x+4.1x=5.7 | | 3.44-1.25=1.05(2.38x+6.81) | | 42x^2+10x=0 | | b=7x(-7) |

Equations solver categories